Accumulative Roll Bonding at Room Temperature of a Bi‐Metallic AA5754/AA6061 Composite: Impact of Strain Path on Microstructure, Texture, and Mechanical Properties1 . Issue 4 (8th June 2017) - Verstraete, Kevin; Azzedine, Hiba; Helbert, Anne‐Laure; Brisset, François; Bradai, Djamel; Baudin, Thierry
Abstract : Accumulative roll bonding (ARB) is performed at room temperature on an aluminum composite up to five rolling cycles, using two different paths: the conventional one (ARB) and the cross ARB (CARB) one consisting of a 90° rotation of the rolling direction before each rolling pass. The microstructure is refined faster by CARB than by ARB occasioning higher yield strength of the elaborated samples. Besides, CARB has the ability to delay the loss of stratification of the composite. The resulting textures are different: while ARB promotes typical rolling components (Brass 011<211>, Goss 110<001>, Dillamore 4 4 11<11 11 8>), S 123<634>), CARB promotes the ND‐rotated Brass 011<755> instead of Brass together with the S and Dillamore components. A Visco‐Plastic Self‐Consistent (VPSC) simulation highlights that the ND‐rotated Brass had Brass and S components for origin. The ND‐rotated Brass presence in the texture promotes a better mechanical isotropy of the composite sheet. Abstract : Accumulative Roll Bonding (ARB) on dissimilar alloys leads to an enhancement of the strength, but the typical fracture of the hard phase interfere with this evolution. A rotation of the sample between each rolling (using CARB) may delay this issue. Besides, two consequences of this rotation are significant: an enhancement of the composite's strength and an original texture.